Donor-acceptor random copolyesters containing perylenebisimide (PBI) and oligo(p-phenylene vinylene) (OPV) by melt condensation polymerization: energy transfer studies - Nisha, S. Kumari; Asha, S. K. (Journal of Physical Chemistry B, 2013)
Novel copolyesters consisting of oligo(p-phenylene vinylene) (OPV) as donor (D) and perylenebisimide (PBI) as acceptor (A) were synthesized by melt polycondensation. Photoinduced energy transfer and photoinduced charge separation in these polyesters were studied in solution as well as in the solid state. Selective excitation of OPV moiety resulted in the energy transfer with >90% efficiency from OPV to PBI chromophore in the solution state. The direct excitation of PBI in the D A copolyester resulted in reduced fluorescence emission of acceptor, indicating electron transfer between the D and A moieties. The effect of distance between donor and acceptor on the energy transfer efficiency from donor to acceptor was studied. Compared to a physical mixture of D and A polyesters alone, the energy transfer was 4 times more efficient in the D A copolyester, highlighting the influence of covalently linking D and A in a single polymer chain. A strong fluorescence quenching (similar to 100%) of both chromophores in solid state indicated an efficient photoinduced charge transfer after photoexcitation of either D or A. Thus, OPV-PBI main chain copolyester is an excellent system for the study of energy- and electron-transfer processes in organic semiconductor. Reactive blend of D/A copolyester was also prepared by the transesterification reaction between D and A alone copolyesters. The energy transfer efficiency from D to A moiety upon selective excitation of D chromophore in the D/A copolyester blend was similar to 4 times higher compared to a physical mixture of D and A alone copolyesters, which gave direct proof for the transesterification reaction in polyester/polyester reactive blending.

Designed amphiphilic polystyrene as surfactant for oligo(p-phenylenevinylene)-incorporated PS nanobeads and visual detection of bilirubin in human blood serum - Makkad, Sarabjot Kaur; Asha, S. K. (ACS Applied Polymer Materials, 2019)
Amphiphilic polystyrene having pendant glucuronic acid (PS-DGlu) was designed and systematically synthesized to be used as a stabilizing agent in styrene miniemulsion polymerization, while covalently incorporating oligo(p-phenylenevinylene) (OPV)-based fluorophore to prepare PSG-OPV-n. This OPV fluorophore was incorporated with an aim to work as a signal transducer, while glucuronic acid on the surface of PS nanobeads would act as the water solubilizing moiety for PS to enable it to function as surfactant and also serve as an interaction site for free bilirubin to facilitate noncovalent interaction via hydrogen bonding. Efficient energy transfer from OPV to bilirubin was observed, owing to the appreciable spectral overlap between emission of OPV and absorption of bilirubin. Visual color change from blue to bluish green was observed under an UV lamp after the addition of bilirubin into the polymer. Selectivity of the sensor was checked among the pool of other interferences, such as glucose, sucrose, metal ions, cholesterol, and biliverdin. The limit of detection was found to be as low as 20 nM, which is far less than the clinical range for causing jaundice (<25 to >50 mu mol/L). Moreover, the developed sensor showed its effectiveness toward real time monitoring of free bilirubin in human serum.
Keywords: amphiphilic homopolymer; bilirubin; functionalized polystyrene nanobeads; oligo(p-phenylenevinylene); sensing

Dual responsive cellulose microspheres with high solid-state fluorescence emission - Yadav, Prashant; Prajitha, K. P.; Dhaware, Vinita; Subramani, Mohan; Joy, Pattayil; Asha, S. K.; Shanmuganathan, Kadhiravan (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2020)
Materials that respond to multiple stimuli such as magnetic field and light are attractive for security and medical diagnostic applications. One of the major challenges in dual functional microspheres is that the presence of magnetic nanoparticles can quench fluorescence emission. Also, there is a probability of solid-state quenching due to the proximity of the fluorophore. We report here a facile approach to prepare cellulose microspheres with high solid-state fluorescence using 40 % tetrabutylammonium hydroxide (TBAH). The fluorescence quenching effect due to the presence of Fe3O4 nanoparticles and solid-state quenching due to aggregation of fluorophore was systematically investigated. Microspheres with the detectable magnetic response and fluorescence quantum yield as high as 0.57 (FMB 414) was obtained by optimizing the reaction conditions. Such a high quantum yield has not been reported before for dual stimuli-responsive fluorescent microspheres. The magnetic and fluorescent properties were found to be durable even after multiple washing cycles. These dual responsive cellulose microspheres can be added as security features to authenticate documents such as passports, degree certificates, currency notes, financial documents etc.
Keywords: Fluorescent; Magnetic; Microcrystalline cellulose; microspheres; Stimuli responsive microspheres; Tetrabutylammonium hydroxide

Direct (hetero)arylation (DHAP) polymerization of conjugated polymers - new A-B-A monomer design for P(NDI2OD-T2) & the challenges of adopting DHAP for continuous flow processes - Kakde, Navnath R.; Bharathkumar, H. J.; Wavhal, Bhaiyyasaheb A.; Nikam, Arun; Patil, Suneha; Dash, Soumya Ranjan; Vanka, Kumar; Krishnamoorthy, K.; Kulkarni, Amol; Asha, S. K. (Journal of Materials Chemistry C, 2022)
P(NDI2OD-T2), also known as Polyera ActivInk N2200, was synthesized by the atom-economic direct hetero arylation polymerization (DHAP) route using a newly designed A-B-A monomer. The new monomer design involved flanking naphthalene diimide with bithiophene units in the bay position, which was further polymerized with bay substituted 1,4-dibromo naphthalene diimide, to afford the same polymer structure as P(NDI2OD-T2). The new monomer design resulted in a very high molecular weight (M-n: 99.5 kDa, D-M: 2.8) defect-free polymer in a quantitative yield by the DHAP batch process using 1,2,4-trichlorobenzene (TCB) as the solvent. DFT studies revealed that the abstraction of the alpha-proton from the naphthalene diimide substituted 2,2 `-bithiophene was favorable by 2.6 kcal mol(-1) (Delta Delta G) as compared to that from 2,2 `-bithiophene. The reason for this improved C-H activation at the alpha position can be attributed to the presence of C-HMIDLINE HORIZONTAL ELLIPSIS pi stabilizing interactions in naphthalene diimide substituted 2,2 `-bithiophene, which strengthens upon the extended charge delocalization throughout the ring, thus stabilizing the conjugate base generated after the proton abstraction. Continuous flow polymerization was carried out by pumping the DHAP reaction mixture including the monomers, catalyst, and additive (pivalic acid) solubilized in degassed TCB through a pre-heated glass condenser packed with K2CO3 and Celite under aerobic conditions. Reproducible molecular weights of M-n: 29.5 kDa, D-M: 1.7 were obtained at much lower concentrations of reactant mixture compared to that for batch polymerization. This is the first report of the synthesis of P(NDI2OD-T2) by a Continuous Flow Process adopting the DHAP route to obtain a defect-free polymer with reasonable molecular weights. P(NDI2OD-T2) was also synthesized by Stille polymerization as a reference control sample to compare the thermal and charge carrier transport properties of the DHAP polymers. Organic field-effect (OFET) mobility measurements indicated mobility values in the order of 10(-3) cm(2) V-1 s(-1) for the DHAP batch polymer (using the novel monomer design). The P(NDI2OD-T2) synthesized by DHAP batch using the commonly used starting materials - bisbromo naphthalene diimide and bithiophene, exhibited OFET mobilities which were one order less, similar to 10(-4) cm(2) V-1 s(-1). This observation highlights the importance of structural design in the monomer to enhance reactivity and thereby the bulk properties using the DHAP route.

Design and synthesis of photocrosslinker and light blocker based on L-Amino acid polyester and their application in solvent-free resin formulation for DLP/SLA 3D printing - Kamble, Ganesh N.; Joshi, Dheeraj Chandra; Asha, S. K. (Polymers, 2023)
Customising material design for new technological applications like additive manufacturing (AM) is a challenging yet promising approach to create a palette of materials suitable for developing eco-friendly products. LGlutamic acid and L-aspartic acid based aliphatic, photocurable polyester crosslinkers were designed and developed and incorporated into a solvent-free photocurable resin formulation with hydroxyl (ethyl)methacrylate (HEMA). Proof-of-concept 3D printing of clear and transparent objects was demonstrated using digital light processing (DLP) and Stereolithography (SLA) techniques. Resolution of the 3D printed objects could be improved by incorporating a Dansyl labelled L-glutamic acid polyester, which not only aided in modulating the viscosity of the resin formulation but could also function as a light blocker, thereby avoiding polymerization of unwanted areas while 3D printing. The curing kinetics of the photocurable formulation was analyzed using photo differential Scanning Calorimetry. Enzymatic degradability studies of 3D printed films were undertaken in PBS buffer containing esterase enzyme and compared with 3D printed samples using HEMA and a commercial crosslinker (Trimethylolpropane triacrylate (TMPTA)). Scanning electron microscopy (SEM) was used to evaluate the morphology of the 3D printed films before and after enzymatic degradation in the PBS buffer for 60 days. The 3D printed amino acid crosslinked films of HEMA presented high degree of degradation in contrast to the near total absence of any degradation in the 3D printed film crosslinked using TMPTA. The availability of new photocurable formulations that are enzymatically degradable are highly sought after for 3D printing applications.
Keywords: 3D printing; Crosslinker; L -Amino acid Polyester; Light blocker; Photocurable